Ohmic contacts to InN-based materials - Sai, P.O. (Технология и конструирование в электронной аппаратуре, 2016)
The key aspects of ohmic contact formation to InN-based materials were investigated. Detailed analysis of studies conducted over the past three decades, allows determining the basic principles of such contacts. The contact structure properties and optimal conditions for them are presented. Different types of metallization are considered, the advantages and disadvantages of each are determined, including the basic requirements that such contact must meet. There is emphasis on the using multilayer metallization with the barrier layers. In the case of the InAlN/GaN systems, the general approaches of forming ohmic contacts were considered. Рассмотрены ключевые моменты в формировании омических контактов к нитрид индиевых пленок, фокусируясь на n-InN и InAlN/GaN гетероструктурах. Детальный анализ исследований, проведенных за последние три десятилетия, позволяет определить основные принципы формирования подобных контактов. Приведены параметры контактов и оптимальные условия их достижения, рассмотрены различные типы металлизации и определены преимущества и недостатки каждого из них, учитывая основные требования, которым подобные контакты должны отвечать. Сделан акцент на перспективах использования многослойной металлизации с диффузионными барьерами. Рассмотрены общие подходы к формированию омических контактов к InAlN/GaN-гетероструктур. В даній роботі розглянуто ключові моменти в формуванні омічних контактів до нітрид-індієвих плівок, фокусуючись на гетероструктурах n-InN і InAlN/GaN. Детальний аналіз досліджень, проведених за останні три десятиліття, дозволив визначити основні принципи формування подібних контактів. Наведено параметри контактів та оптимальні умови їх досягнення, розглянуто різні типи металізації і визначено переваги та недоліки кожного з них, враховуючи основні вимоги, яким подібні контакти мають відповідати. Наголошено на перспективах використання багатошарової металізації з дифузійними бар’єрами. Розглянуто загальні підходи формування омічних контактів до InAlN/GaN-гетероструктур.